Corporate governance and innovation: a theoretical review. Issue 3 (7th October 2019) - Asensio-López, Diego; Cabeza-García, Laura; González-Álvarez, Nuria
Abstract : Purpose: The purpose of this paper is to present a review of the literature on two lines of research, corporate governance and innovation, explaining how different internal corporate governance mechanisms may be determinants of business innovation. Design/methodology/approach: It explores the theoretical background and the empirical evidence regarding the influence of both ownership structure and the board of directors on company innovation. Then, conclusions are drawn and possible future research lines are presented. Findings: No consensus was observed regarding the relation between corporate governance and innovation, with both positive and negative arguments being found, and with empirical evidence not always pointing in the same direction. Thus, new studies trying to clarify this relationship are needed. Originality/value: Over recent years, interest has grown in the influence of governance mechanisms on innovation decisions taken by the management. Innovation efforts and results depend on factors that are influenced by corporate governance, such as ownership structure or the functioning of the board of directors. Thus, the paper shows an updated state of the art in this field proposing future lines for empirical research.